Keberkesanan aktiviti dakwah dalam aplikasi tiktok terhadap akhlak mahasiswa - Fatin Farzana Dass Meral,; Safinah Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This trend of modernization is getting more lively with unlimited sharing. The dai need to be aware that their duties not only in the real world but also in the virtual world need to be continued so that they can preach with the will of mad'u but still remain with the concept of Amar maaruf nahi mungkar. The TikTok application is a new space for dais to venture into a more creative da'wah field. This study aims to examine the involvement of students in preaching on the Tiktok application. This study was conducted using a quantitative approach which is in the form of a survey. This study uses a quantitative method which is a survey based on instruments submitted through a questionnaire. The instrument distribution method involved a total of 45 respondents among specialized students at the Faculty of Islamic Studies Civilization, KUIS. This study shows that Tiktok can be used for preaching purposes such as live, video, and others. This, finds the effectiveness of online preaching, especially the Tiktok application on the morals of students, and should be emphasized by every student. The researcher hopes that future researchers can study the effectiveness of preaching in the YouTube application against families to achieve greater objectives and more extensive research findings.